Oral care medications for the prevention and treatment of ventilator-associated pneumonia in intensive care unit - Huang, Hua; Yu, Xiaomin; Huang, Chenxi; Zeng, Jumei; Li, Yuqing (Frontiers in Oral Health, 2025)
This study aims to ameliorate the management of VAP in clinical practice and deliver more precise care in the ICU. Study selection using the appropriate critical appraisal tools was undertaken by three authors. This review provides an overview of empirical antibiotics, chlorhexidine, and povidone-iodine, which are currently commonly used in critical care. It also discusses oral medications and preparations that may be used to prevent and treat ICU ventilator-associated pneumonia, including new antibiotics, hydrogen peroxide solutions, sodium bicarbonate, octenidine, and oral herbal medicines. It also discusses ongoing research and potential applications, such as the antimicrobial effects of these agents in ICU oral hygiene. Pharmaceuticals and formulations used in oral hygiene are effective or have huge application potential in the prevention and treatment of VAP, but further research is needed to standardize oral health assessment and care practices to develop evidence-based personalized oral hygiene for critically ill patients.